Kajian Yuridis Penjualan Warisan oleh Ahli Waris yang belum terbagi berdasarkan KUH-Perdata - Rochman, Muhammad Syaiful; Ardhana, Fahmi (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Inheritance is one of the most influential legal activities in Indonesia. The purpose of transferring property from one person to another is to provide for someone who has been abandoned by family members. Therefore, it is necessary to share the balance between the heirs and the heirs. This often causes conflicts between heirs, some feel that the assets distributed are not in accordance with their rights, and there are even heirs who have experienced problems with their own assets in the past. own interests, without prior agreement with other heirs.